Boundedness and Asymptotic Stability for the Solution of Homogeneous Volterra Discrete Equations - E. Messina; A. Vecchio (Discrete Dynamics in Nature and Society)
We consider homogeneous linear Volterra Discrete Equations and we study the asymptotic behaviour of their solutions under hypothesis on the sign of the coefficients and of the first- and second-order differences. The results are then used to analyse the numerical stability of some classes of Volterra integrodifferential equations.